Politicians and Rhetoric - Charteris-Black, J. author. aut Link
XII, 239 p.
Keywords: This book analyzes the rhetoric of speeches by major British or American politicians and shows how metaphor is used systematically to create political myths of monsters, villains and heroes. Metaphors are shown to interact with other figures of speech to communicate subliminal meanings by drawing on the unconscious emotional association of words.